2017
DOI: 10.1111/gcb.13726
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation

Abstract: Methane (CH ) emissions from tropical wetlands contribute 60%-80% of global natural wetland CH emissions. Decreased wetland CH emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño-Southern Oscillation (ENSO) on CH emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models' projections. We use a process-based model of global wetland CH emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…However, good overall agreement of model simulations with different observations, including the ability of the model to simulate the observed atmospheric responses to El Niño events (i.e. OEI change of 2.8 DU compared to 2.4 DU in Ziemke et al, 2010), provides confidence in model performance and results.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…However, good overall agreement of model simulations with different observations, including the ability of the model to simulate the observed atmospheric responses to El Niño events (i.e. OEI change of 2.8 DU compared to 2.4 DU in Ziemke et al, 2010), provides confidence in model performance and results.…”
Section: Discussionmentioning
confidence: 70%
“…We have also assessed the capability of TOMCAT-GLOMAP to simulate observed responses to El Niño events. Ziemke et al (2010) derived an O 3 ENSO index using satellite observations, finding that for a +1 K change in the Niño 3.4 index, there was a 2.4 DU increase in the Ozone ENSO Index (OEI). In TOMCAT-GLOMAP, we calculate a 2.8 DU increase per +1 K in the Niño 3.4, indicating a slightly larger but comparable response to El Niño events.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emissions from natural wetlands have been shown to be the dominant process, with emissions from fires and changes to the atmospheric sink also playing important roles (Bousquet et al, 2006;Chen and Prinn, 2006;Dlugokencky et al, 2011;Kirschke et al, 2013;McNorton et al, 2016;Corbett et al, 2017). These natural sources are climate sensitive, so interannual changes to temperature and precipitation affect the amount of CH4 emitted into the atmosphere as well as the spatial distribution (Zhu et al, 2017). Studies have found that biomass burning emissions are largely responsible for the IAV of carbon monoxide (CO) and also affect O3 concentrations (Granier et al, 2000;Monks et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%